2022
DOI: 10.3390/app12178692
|View full text |Cite
|
Sign up to set email alerts
|

Safety Risk Assessment of Highway Bridge Construction Based on Cloud Entropy Power Method

Abstract: (1) In recent years, with China’s increasing investment in the transportation industry, the construction of highways and bridges has flourished, bringing great convenience to people’s lives. At the same time, there are many uncertain factors in the process of bridge construction, being prone to construction risks. In order to meet the requirements of sustainable development, it is necessary to accurately evaluate the safety risk level of bridge construction. Therefore, it is necessary to establish a new scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The entropy weight method (EWM) was adopted in the objective part. The basic principle of EWM is to determine the weight of each index based on the size of target information contained in each index [21]. Finally, subjective and objective preference coefficients were introduced to obtain the comprehensive index weight of fire safety resilience of residential self-built houses [22].…”
Section: Establish Weight 321 Calculation Methodsmentioning
confidence: 99%
“…The entropy weight method (EWM) was adopted in the objective part. The basic principle of EWM is to determine the weight of each index based on the size of target information contained in each index [21]. Finally, subjective and objective preference coefficients were introduced to obtain the comprehensive index weight of fire safety resilience of residential self-built houses [22].…”
Section: Establish Weight 321 Calculation Methodsmentioning
confidence: 99%
“…Ji et al [ 10 ] based on the Yinzhou Lake Bridge project, identified sources of risk within divisional work and conducted risk prioritization. Li et al [ 11 ] constructed evaluation models to assess the construction safety risks of highway bridges. Jin et al [ 12 ] conducted an evaluation of grouting effectiveness in karst areas, considering the construction technology, apparent parameters, observational data from inspection holes and geophysical exploration techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The method showed satisfactory results in various performance indicators such as flood delay, energy efficiency and throughput. Li et al 22 established a risk assessment index system for safety in the operational phase of highway bridges. They then used cloud entropy weighting to objectively weigh various risk indicators and applied cloud model theory to risk assessment, emphasizing the objectivity of the assigned values.…”
Section: Introductionmentioning
confidence: 99%